Make me yours, cowboy - Crush, Dylann (Crush, Dylann. Cowboys in paradise, 2023)
Arriving on Paradise Island to work on his new album, country superstar Knox Shepler, posing as a contractor to hide his true identity, is forced to work with Claudia Alvarez, and as they spend their days together, he finds inspiration and more in this beautiful woman until the truth comes to the surface.